Signifikasi Wawasan Nusantara Dalam Membangun Warga Negara Yang Baik Di Era Globalisasi - Afifah Az-Zahra Harahap; Nayla Sagita; Yerni Maria Pakpahan (Jurnal Pengetahuan Sosial dan Sejarah, 2026)
Globalization has a significant impact on national life, one of which is marked by the decline in the spirit of nationalism and the increasing tendency of individualism. In this situation, the Indonesian archipelago perspective has a vital role as a way of life for the Indonesian nation that is based on the values of Pancasila and the 1945 Constitution, in order to strengthen unity in facing global challenges. This article reviews the importance of the Indonesian archipelago perspective in forming the character of ideal citizens, which is reflected through an attitude of love for the homeland, loyalty to the state, tolerance, and upholding democratic values. In addition, the discussion also emphasizes the importance of the active role of society in maintaining national identity through education, social involvement, and compliance with legal regulations. By making the Indonesian archipelago perspective the foundation of nationality, it is hoped that the noble values of the Indonesian nation will be maintained amidst the dynamics of globalization.